Action Items for Breast Cancer Awareness Month - Deanna J. Attai (Journal of Patient-Centered Research and Reviews, 2020)
This special issue introduction provides a brief history of Breast Cancer Awareness Month and focuses on patient populations often omitted from annual marketing campaigns. The importance of research is emphasized as a means to improve the outcomes of people with metastatic breast cancer and male breast cancer as well as to address health care inequities related to breast cancer diagnosis and treatment.